2017
DOI: 10.3390/ijms18061134
|View full text |Cite
|
Sign up to set email alerts
|

A Relative Deficiency of Lysosomal Acid Lypase Activity Characterizes Non-Alcoholic Fatty Liver Disease

Abstract: Lysosomal acid lipase (LAL) is a key enzyme in lipid metabolism. Initial reports have suggested a role for a relative acquired LAL deficiency in non-alcoholic fatty liver disease (NAFLD)—however, it is still unclear whether this mechanism is specific for NAFLD. We aimed to determine LAL activity in a cohort of NAFLD subjects and in a control group of hepatitis C virus (HCV)-infected patients, investigating the role of liver cirrhosis. A total of 81 patients with a diagnosis of NAFLD, and 78 matched controls wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…These findings confirm the results from previous studies showing a significant reduction of LAL activity in NAFLD patients, compared to HS, with a further reduction in the subgroup of those with NASH . In particular, patients with NAFL had a 27.0% reduction in LAL activity, which increased to 41.8% in the subgroup of patients with biopsy‐proven NASH.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings confirm the results from previous studies showing a significant reduction of LAL activity in NAFLD patients, compared to HS, with a further reduction in the subgroup of those with NASH . In particular, patients with NAFL had a 27.0% reduction in LAL activity, which increased to 41.8% in the subgroup of patients with biopsy‐proven NASH.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies showed a progressive decrease in LAL activity from healthy subjects (HS) to subjects with NAFL and those with biopsy‐proven NASH . More recently, in patients with cryptogenic cirrhosis (CC), a further reduction in the activity of LAL has been described .…”
Section: Introductionmentioning
confidence: 98%
“…More recently, Tovoli et al[31] performed a study of LAL activity in 81 patients with a diagnosis of NAFLD and 78 matched controls with HCV-related liver disease. LAL activity was significantly reduced in NAFLD compared to that in HCV patients, suggesting that NAFLD is characterized by a specific deficit in LAL activity.…”
Section: Lal Activity Reduction and Nafldmentioning
confidence: 99%
“…They found a significant reduction in LAL activity in NAFLD patients and the enzyme activity was significantly worse in the subgroup of patients with biopsy-proven non-alcoholic steatohepatitis (NASH). More recently, Tovoli et al [18] demonstrated that this deficiency is specific to NAFLD by comparing NAFLD patients with HCV-infected patients, particularly in the pre-cirrhotic stage of disease.…”
Section: Introductionmentioning
confidence: 99%